Ali se izvedenec lahko moti - Sever, Alenka (Podjetje in delo, 2014)
The work of an expert witness calls for great responsibility, thus making any errors which may have been done by an expert witness not only unpleasant, but also resulting in far-reaching consequences. The author makes reference to a part of international guidelines which are similar or even identical with regard to several guidelines: (1) the expert is to identify the expert problem, as well as (2) the differences between a clinical exam and the exam carried out in the process of preparation of an expert opinion; (3) employment of multiple resources and information; (4) the use of scientifically supported psychodiagnostic procedures with adequate psychometric characteristics; (5) the need for expert's own self-restriction. The author also brings attention to particularly delicate areas - expert witnesses dealing with pre-school children as well as persons with a mildly traumatic brain injury, and especially to the difficulties an expert witness faces in cases involving violent acts.
Keywords: izvedenstvo; sodišča; sodna zmota; sodni postopek